O que pode o consultório na rua? Considerações a partir da clínica da atividade - Curvo, Daniel Rangel (2018)
Based on the Clinic of Activity‘s theory and methods perspective, this work investigates the development of the power of action of professionals from the Street Clinic (SC) program. SC Program is part of the Brazilian Public Health System‘s (SUS) Primary Care program, created in 2012 in order to foster the integral care of homeless people. The investigation utilizes both the Instruction to a Double and Photography Workshop methods, as is done by the Clinic of Activity. A total of 14 professionals and 4 teams participated in the research process. The results indicate work teams as professional genres that owe transpersonal patrimony, both technical and affectionate, that operate the production of work processes. Use of emotional bond is highlighted for amplifying care in personal relations that permeate work. The perceptive changes related to prejudice towards homeless people should also be stressed, as a personal assumption of a successfully developed work. Ethic-political fears were the emotions that mostly called attention to. Fear was commonly repurposed, promoting protective actions instead of distance with homeless people. Ethic-political issues turned out to be an action mobilizer, adding sense to the researchers‘ work. Also, Street Clinics are revealed as a task that provokes professionals to enhance their power of action. In addition, fosters the constitutional principles of SUS. However, some elements were proven to limit this enhancement, such as discrimination in services, intrapersonal difficulties in hierarchy relations, and frailty of employment bonds. It could be verified that teams mostly perform towards actions to halt health issues from aggravating and less frequently regarding the diseases' social determinations or to promote healthcare. Clinic of Activity method was proven valuable. Professionals request its use to be continued as an alternative to care for teams and professionals of SC. Finally, understanding homeless people as an expression of the social conditions and Street Clinics as new and strategic work, we emphasize the relevance of continuous studies to deepen the investigation raised in this work.